Interface entre frame, metáfora conceitual e estrutura simbólica: conceitualizações de aprendizagem da língua inglesa - Silva, Teófilo Roberto da (2018)
The present research aimed to demonstrate the theoretical and methodological feasibility of a triple interface between the frame theory of Barsalou (1992b), Lakoff and Johnson's Theory of Conceptual Metaphor (TMC) (1980, 1999), and the notion of symbolic structures, according to Langacker (1987, 2008). The interface was operationalized to identify how English language learners – undergraduate students of the Federal Institute of Education, Science and Technology of Ceará – use metaphors to understand the process of language learning. The data analyzed consisted of transcribed discussions, collected in two focus groups. The informants had all been participants in the Science without Borders program in English-speaking countries. The theoretical framework consists of an interface of Conceptual Metaphor Theory (TMC), by Lakoff and Johnson (1980, 1999), with the frames perspective of Barsalou (1992b). For analytical procedures, the theoretical-methodological interface was made possible through the concept of symbolic structure (LANGACKER, 1987, 2008). In this sense, the present study does not consider the lexical unit as a unit of analysis, its unit of analysis is the symbolic structure, which is not necessarily manifested in lexical unity. In this aspect, the research distances itself from the tendency common to the studies of the metaphor. The diversity of informants' experiences allowed us to identify conceptualizations in the context of instructional learning and in the context of non-instructional learning. In the first case, the analyzes revealed the predominance of negative understandings with metaphors strongly based on the notion of object. In the second case, positive understandings of learning predominated, and emerging metaphors were consistently based on the notion of movement. These characteristics were diffused in the context of learning the language in a specialized course. The investigations demonstrated the suitability of the theoretical interface. The frame model proposed by Barsalou (1992b) was not only a theoretical tool with a strong contribution potential for TMC but also compatible with the characterization of Langacker's symbolic structures (1987, 2008). We consider the theoretical-methodological interface an important contribution of this research.